A study of adventitious contamination layers on technically important substrates by photoemission and NEXAFS spectroscopies. (February 2018) - Sinha, Sumona; Mukherjee, M.
Abstract: This paper addresses the study of adventitious contamination layers on the technically important substrates by X-ray and UV photoemission (XPS and UPS) as well as near-edge X-ray absorption fine structure (NEXAFS) spectroscopies. This investigation draws attention with regard to its application in the electronic devices of lower dimension. The Au, Pt, Ag, Cu, H passivated and SiO2 coated Si (100) are used as substrates. The XPS studies reveal that the composition of the adventitious contamination layer on studied noble substrates is distinct from those of non-metallic (H passivated and SiO2 coated Si) substrates. The ratio of the composition is different for various noble metal substrates. Furthermore, chemisorbed oxygen layer is found to present on Pt, Ag and Cu substrates in contrast to Au one. Our UPS results expose that the valence electronic structure, as well as workfunction of noble metal surfaces, are modified due to the contamination layer onto the substrate surfaces. The C K-edge NEXAFS spectra from the contamination layers on several substrates are presented to exhibit that the composition of contamination layer is different on different substrates whereas angle dependent NEXAFS data suggests that adventitious contamination layers on all substrates are amorphous in nature. Highlights: Composition of the adventitious contamination layer on noble metal substrates is different from passivated Si (100) wafers. The ratio of the composition is different for various noble metal substrates. Valence band and workfunction of noble metal surfaces are modified for the presence of contamination layer on the substrates. Adventitious contamination layer is amorphous in nature. Different C-K edge NEXAFS spectra is found from contamination layer onto the various substrates.